Noninvasive methods to determine the critical micelle concentration of some bile acid salts - Reis, Salette (2019)
In this work the critical micelle concentrations (cmc) of four bile salts, sodium cholate, sodium glycocholate, sodium deoxycholate, and sodium glycodeoxycholate, are determined and presented. Three independent noninvasive methodologies (potentiometry, derivative spectrophotometry, and light scattering) were used for cmc determination, at 25 degrees C with ionic strength adjusted to 0.10 M with NaCl. Spectrophotometric and potentiometric studies of some bile salts were also executed at various ionic strength values, thus allowing the influence of the ionic strength on the cmc value of the bile salt to be assessed. A critical comparison of the cmc values obtained with data collected from the literature is presented. Furthermore, this work makes an evaluation of the conceptual bases of different methodologies commonly used for cmc determination, since variations in the results obtained can be related mainly to different intrinsic features of the methods used (such as sensitivity or the need to include tracers or probes) or to the operational cmc definition applied. The undoubted definition of the experimental bile salt concentration that corresponds to cmc (operational cmc) is essential since in the case of these amphiphiles the formation of micelles is not as abrupt as in the case of ordinary association colloids. The biphasic nature of their aggregation leads to a "round-shaped" variation of the experimental parameters under analysis, which makes difficult the evaluation of the cmc values and can be responsible for the different results obtained.